Gastric Antisecretory, Antiulcer And Cytoprotective Properties Of Tamira Parpam (Bio-Copper) From Earthworm - M.KRISHNAVENI,; J.ANBU,; S.NITHYA,; ASHWINI ANJANA,; S.PREMA, (International Journal of Pharma and Bio Sciences, 2012)
In the present study we investigated the anti-ulcer properties of Tamira Parpam (bio-copper) from earthworm against Aspirin plus pylorus ligation induced gastric ulcer in rats, HCl-Ethanol induced ulcer in mice and water immersion stress induced ulcer in rats. The number of lesions in HCI-Ethanol induced peptic ulcer model and mean score value of ulcer inhibition in water immersion stress induced ulcer model. A significant antiulcer activity of Tamira Parpam was observed in all the models. Pylorus ligation model showed significant reduction in gastric volume, free acidity and ulcer index as compared to control. Results revealed that the Tamira Parpam showed significant (P<0.01) ulcer inhibition in HCl-Ethanol induced ulcer and ulcer protection index (P<0.01) in stress induced ulcer. This study indicates that Tamira Parpam have potential anti-ulcer activity in the three models tested.